FABP1 knockdown in human enterocytes impairs proliferation and alters lipid metabolism - Rodriguez Sawicki, Luciana (2017)
Fatty Acid-Binding Proteins (FABPs) are abundant intracellular proteins that bind long chain fatty acids (FA) and have been related with inmunometabolic diseases. Intestinal epithelial cells express two isoforms of FABPs: liver FABP (LFABP or FABP1) and intestinal FABP (IFABP or FABP2). They are thought to be associated with intracellular dietary lipid transport and trafficking towards diverse cell fates. But still their specific functions are not well understood.To study FABP1´s functions, we generated an FABP1 knockdown model in Caco-2 cell line by stable antisense cDNA transfection (FABP1as). In these cells FABP1 expression was reduced up to 87%. No compensatory increase in FABP2 was observed, strengthening the idea of differential functions of both isoforms. In differentiated FABP1as cells, apical administration of oleate showed a decrease in its initial uptake rate and in long term incorporation compared with control cells. FABP1 depletion also reduced basolateral oleate secretion. The secreted oleate distribution showed an increase in FA/triacylglyceride ratio compared to control cells, probably due to FABP1´s role in chylomicron assembly. Interestingly, FABP1as cells exhibited a dramatic decrease in proliferation rate. A reduction in oleate uptake as well as a decrease in its incorporation into the phospholipid fraction was observed in proliferating cells.Overall, our studies indicate that FABP1 is essential for proper lipid metabolism in differentiated enterocytes, particularly concerning fatty acids uptake and its basolateral secretion. Moreover, we show that FABP1 is required for enterocyte proliferation, suggesting that it may contribute to intestinal homeostasis.